PENGARUH PELAYANAN TERHADAP TINGKAT KEPUASAN PELANGGAN DI APOTEK ARFATHAN FARMA TAHUN 2024 - Andriana, Yuni; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Fathurrahman; Lale Ajeng Khalifatun Wardani (Nusadaya Journal of Multidiciplinary Studies, 2024)
This study shows that service has a significant influence on customer satisfaction at Arfathan Farma Pharmacy. The results of statistical tests prove that good service significantly increases customer satisfaction, with a significance value of 0.000 and a ttest of 3.986. In addition, each one-unit increase in service can increase customer satisfaction by 0.606 units. However, service only contributes 24.9% to customer satisfaction, while the remaining 75.1% is influenced by other factors such as price, product quality, facility comfort, employee friendliness, pharmacy location, and customer personal factors that were not examined in this study.